[Sunday afternoon, kicking it with my homies] - Cayetano Contreras, Jr.::::::::: (2005)
Description supplied by photographer: "Domingo en la tarde. Pasando un buen rato con mis amigos." Translation of description: "Sunday afternoon, kicking it with my homies."